2008
DOI: 10.1038/sj.ki.5002794
|View full text |Cite
|
Sign up to set email alerts
|

A novel renal carbonic anhydrase type III plays a role in proximal tubule dysfunction

Abstract: Dysfunction of the proximal tubule (PT) is associated with variable degrees of solute wasting and low-molecular-weight proteinuria. We measured metabolic consequences and adaptation mechanisms in a model of inherited PT disorders using PT cells of ClC-5-deficient (Clcn5Y/-) mice, a well-established model of Dent's disease. Compared to cells taken from control mice, those from the mutant mice had increased expression of markers of proliferation (Ki67, proliferative cell nuclear antigen (PCNA), and cyclin E) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…12,13 In addition to defective apical transport, abnormal proliferation is often observed in diseased PT cells. 13,24,33 Increased proliferation was consistently observed in kCH kidneys and mPTCs exposed to RFS-kLCs as indicated by the PCNA and cyclin-D1 markers and bromodeoxyuridine incorporation. Our data suggest the involvement of the Y-box transcription factor ZONAB, which is active during nephrogenesis and PT maturation.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…12,13 In addition to defective apical transport, abnormal proliferation is often observed in diseased PT cells. 13,24,33 Increased proliferation was consistently observed in kCH kidneys and mPTCs exposed to RFS-kLCs as indicated by the PCNA and cyclin-D1 markers and bromodeoxyuridine incorporation. Our data suggest the involvement of the Y-box transcription factor ZONAB, which is active during nephrogenesis and PT maturation.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that a delicate balance between factors involved in proliferation and others involved in differentiation operates in PT cells. 24 The balance can be defective, for instance, in cystinosis, where increased proliferation and dedifferentiation of PT cells are associated with abnormal activity of ZONAB caused by defective intercellular junctions. 13 This study does not provide a direct correlation between increased rate of proliferation and dedifferentiation of PT cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3]), type 3 carbonic anhydrase (CAIII, from Ref. [8]) or Tamm-Horsfall protein (UMOD, from Ref. [15]).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to Dent's disease, genetic inactivation of Clcn5 in mouse induces a severe trafficking defect in PT cells, with loss of megalin and cubilin at the brush border and LMW proteinuria [7]. Furthermore, ClC-5 inactivation causes urinary excretion of type 3 carbonic anhydrase (CAIII) [8]. CAIII has been uniquely detected in the urine of ClC-5-or megalin-deficient mice and patients with Dent's disease.…”
Section: Introductionmentioning
confidence: 99%